PENGARUH PEMBELAJARAN BERBASIS PROJEK PADA MATA PELAJARAN LANSKAP DAN PERTAMANAN DALAM DIMENSI PROFIL PELAJAR PANCASILA DI SMK NEGERI 1 BAWEN - Khairunisa, Aulia; Nur Wahyunani, Atip (Jurnal Biogenerasi, 2025)
The Merdeka Curriculum is a curriculum that is contextualised to current conditions. It is hoped that with a contextualised project base that is applied, students can better implement knowledge in everyday life. The purpose of this study is to analyse the relationship between the implementation of PjBL and learning activities in Landscape and Landscaping subjects. This type of research is descriptive qualitative with the research subjects being students of Class XI ATP B at SMK Negeri 1 Bawen. The technique used is convenience sampling with an observation sheet instrument. The results of PjBL application can be seen in the learning activities and daily life of the students in school. In addition, the use of PjBL can also promote and develop the attitudes that exist in the dimensions of the Pancasila Student Profile.